2016
DOI: 10.1103/physreve.94.052143
|View full text |Cite
|
Sign up to set email alerts
|

Metastable minima of the Heisenberg spin glass in a random magnetic field

Abstract: We have studied zero-temperature metastable minima in classical m-vector component spin glasses in the presence of m-component random fields for two models, the Sherrington-Kirkpatrick (SK) model and the Viana-Bray (VB) model. For the SK model we have calculated analytically its complexity (the log of the number of minima) for both the annealed case where one averages the number of minima before taking the log and the quenched case where one averages the complexity itself, both for fields above and below the d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 33 publications
0
17
1
Order By: Relevance
“…4b). The test consists to validate the Edwards measure in the metastable states as done in (Sharma et al, 2016), following the use of the Edwards assumption to calculate the ground state of the hard sphere model in (Charbonneau et al, 2014b) and using the exact results of (Newman and Stein, 1999). This test can be done for the 1-SF metastable state in the exactly solvable Sherrington-Kirkpatrick (SK) spin-glass model (Sherrington and Kirkpatrick, 1975), which is the canonical mean field model of spin glasses.…”
Section: The Rigorous Results Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…4b). The test consists to validate the Edwards measure in the metastable states as done in (Sharma et al, 2016), following the use of the Edwards assumption to calculate the ground state of the hard sphere model in (Charbonneau et al, 2014b) and using the exact results of (Newman and Stein, 1999). This test can be done for the 1-SF metastable state in the exactly solvable Sherrington-Kirkpatrick (SK) spin-glass model (Sherrington and Kirkpatrick, 1975), which is the canonical mean field model of spin glasses.…”
Section: The Rigorous Results Ofmentioning
confidence: 99%
“…3. The analytical study in (Sharma et al, 2016) of zero-temperature metastable minima in classical Heisenberg spin glass in a random magnetic field. Such a study confirms that the energy reached dynamically is in agreement with a computation of metastable states using Edwards equiprobability, see Eq.…”
Section: Opening Pandora's Box: Test Of Edwards Uniform Measure Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Our interest in the static aspects of SOC behavior was triggered by our previous studies [23] of vector spin glasses in the Sherrington-Kirkpatrick (SK) model. We found that the quench in those models reached metastable minima whose energy per spin E c was very close to that calculated for the energy which separates minima with zero overlap with each other from those which have a full replica symmetry overlap with each other [24].…”
Section: Introductionmentioning
confidence: 99%
“…What led us to carry out this investigation was the work of Sharma et al [15,16]. It was found in these papers that a quench from an initial random (i.e.…”
Section: Introductionmentioning
confidence: 99%